Drivers of migration intentions in the Volta Delta: Investigating the effect of climate-related hazards and adaptation strategies - Abu, Mumuni; Atiglo, D. Yaw; Addoquaye Tagoe, Cynthia; Codjoe, Samuel N. (Frontiers in Climate, 2022)
The decision to migrate involves multiple causes and motivations with environmental factors subsumed by economic and other dimensions. Deltas are rich in natural resources but are also vulnerable to environmental hazards making them a hotspot for out-migration. In spite of some infrastructural interventions, specifically in the Volta Delta, to minimize the environmental effects, there is scant evidence of their impacts on livelihoods and the potential to reverse out-migration trends and aspirations. Additionally, there is little knowledge on the key drivers of migration in the area. Using data from the 2016 DECCMA household survey in Ghana, we found that exposure to drought does not trigger migration intentions, however, exposure to erosion and salinity do. Households capable of diverse adaptation options have a higher likelihood of migration intention. Households whose main livelihood is ecosystem-based were less likely to have the intention to migrate compared with those whose livelihoods were non-ecosystem based. The study provides insights into future migration intentions and drivers of migration in the Volta Delta.